Новый род и два новых вида щелкунов (Coleoptera, Elateridae) из трибы Pleonomini - Гурьева, Е.Л. (Вестник зоологии, 1976)
In the Pleonomini tribe one new genus Lomopneus and two new species (L. gracilis and L. mundus) are described. The new genus is close to Pleonomus, differs from it by shorter antennae, the absence of tuberculum near its bases, the presence of the process on the hind angle of pronotum (Fig. A1; 51), the form of hind process of pronotum (Fig. A2-3; 52-3) and form mesosternal cavity as well as by shorter tarsi and form of the 5th abdominal sternite (Fig. A4; 54). The type species Lomopneus gracilis Gur. sp. n.